Issues surrounding teachers' readiness in implementing the competency-based 'O' Level Geography Syllabus 4022 in Zimbabwe - Chanda, Paul; Mafugu, Tafirenyika (Society for Research and Knowledge Management Ltd, 2022)
The qualitative study, which involved a multiple case study design, focused on the issues surrounding the readiness of teachers to implement the competency-based O-Level Geography Syllabus 4022 in the Zimbabwe secondary school system. In adopting a multiple case study design, the research sought to solicit the opinions of all Geography teachers in the Kwekwe district of Zimbabwe on their readiness to implement the competency-based O-Level Geography Syllabus 4022. A technique involving an analysis of primary documents published by MoPSE was done, and ten in-depth interviews with Geography teachers drawn from two secondary schools and two Focus Group Discussions (FDGs) from the same schools were adopted to generate data. The study established that the updated O-Level Geography Syllabus 4022 was introduced without enough consideration of the readiness of teachers for its implementation. It also emerged from the study that the breadth and depth of the issues surrounding teacher readiness to implement an updated syllabus require action to be taken from several fronts to ensure that the subject community is ready for its rapid delivery. Finally, the research paper recommends massive advocacy and sensitisation of O-Level Geography teachers who are at the helm of the user system to allow for effective delivery of the O-Level Geography Syllabus 4022 in the secondary school sector in Zimbabwe.
Keywords: Readiness; Educator; Competency-based; Syllabus; Geography